Proceedings of the 6th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2014
DOI: 10.1145/2667317.2667320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 'Expert Mode' Voice Command System on Task Performance, Glance Behavior & Driver Physiology

Abstract: Multi-function in-vehicle interfaces are an increasingly common feature in automobiles. Over the past several years, these interfaces have taken on an ever-greater number of functions and the ways in which drivers interact with information have become more complex. Parallel with these technical developments, interest in ensuring that these systems minimize demand placed upon the driver has also increased. Voice command capability has become a popular and desirable feature, as interacting with a vehicle interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 9 publications
(12 reference statements)
5
39
0
Order By: Relevance
“…The driver's face was video-recorded at 30Hz. This recording was used to manually code the driver's eye glances, as described in Reimer et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The driver's face was video-recorded at 30Hz. This recording was used to manually code the driver's eye glances, as described in Reimer et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Sawyer et al (2016) and Reimer et al (2014) showed that despite reduced glances off-road relative to use of a visualmanual human-machine interface (HMI), voice-based interactions with HMIs often have a significant visual component. Four glance metrics were considered, as detailed in Table 1.…”
Section: Glance Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is more time intensive, and suffers from the entropy that human decision-making and response time may inject. Double coding, and use of interrater reliability scores is highly advised (as explored in the context of glance coding in Reimer et al, 2014). Subtask data can, in some cases, involve subsecond epoch lengths, and it is important to consider the synchronicity of clocks responsible for coding various aspects of human and machine performance (for an expanded discussion, see Sawyer et al, 2015).…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…Many experimental studies have investigated the effect of different types of stimulus-response tasks on driving performance (e.g., Angell et al, 2006;Shutko, Mayer, Laansoo, & Tijerina, 2009;Young, Hsieh, & Seaman, 2013;Reimer et al, 2014b). According to the literature, visual and auditory modalities are two of the most frequently used information presentation channels in the in-vehicle secondary tasks, whereas manual and speech (or verbal) input techniques are the most common responding methods.…”
Section: Introductionmentioning
confidence: 99%